PEMBELAJARAN INTERAKTIF MENGENAL ANEKA RAGAM IKAN HIU DENGAN METODE COMPUTER BASED INSTRUCTION - Muhammad Muharrom; Bonny Mulyawan (Indonesian Journal of Business Intelligence (IJUBI), 2019)
This animal recognition learning material is sometimes studied without visual aids or animations making it difficult for students to understand more deeply related to the correct type. Based on the problems above, the writer tries to make an interactive learning in helping the learning process of introducing shark mikan sports. The method of developing multimedia learning materials used is the Computer Based Instruction method where this application can be used to study the types of sharks with a combination of text, graphics, video, sound, and animation. This interactive learning application also provides several interactive games. This Interactive Learning is made using Adobe Photoshop, Adobe Flash CS6.